Cartilage imaging of the hand and wrist using 3-T MRI - Weber, Marc-André; Stillfried, Falko von; Kloth, Jost; Rehnitz, Christoph (Seminars in musculoskeletal radiology, 2012)
The prevalence of osteoarthritis of the hand and wrist is high, and a thorough assessment of even subtle cartilage injuries is necessary before surgical interventions. Although magnetic resonance imaging (MRI) has been established as an important diagnostic tool for the evaluation of hand and wrist disorders, the focus has been on the assessment of the triangular fibrocartilage complex, tendons, ligaments, and the detection of avascular necrosis or occult fractures rather than on cartilage imaging. 3-T MR systems have become more and more widely available and yield an improved signal-to-noise ratio and thus a higher spatial resolution than 1.5-T systems. In principle, this should be especially beneficial for depicting the thin cartilage layers of the hand and wrist. This review focuses on cartilage imaging of the hand and wrist with 3-T MRI and addresses these four topics: (1) the advantages of 3-T versus 1.5- and 1-T MRI, (2) dedicated sequence protocols at 3 T including novel three-dimensional sequences, (3) imaging findings in common cases of overuse or sports injury, and (4) functional cartilage imaging techniques of the hand and wrist, for instance, delayed gadolinium-enhanced MRI of the cartilage.
Gesehen am 02.04.2019